DESIGN AND CONSTRUCTION OF FRAUNHOFER INTERFERENCE-DIFFRACTION APPARATUS FOR SENIOR HIGH SCHOOL PHYSICS EXPERIMENT - SUSANTO (NIM 20206041), EDI
Interference-diffraction phenomenon is one of nature phenomenon that is often met in life, especially in the field of optics. When coherent light passing through one or more narrow slit or apertures, dark and bright pattern are shown at screen behind the slit. From this pattern, the wavelength, the slit width and the distance between slits can be calculated. In this final project, we design and construct an apparatus to observe the interference-diffraction phenomenon. This appartus is intended to assist students to understand the interefernce-diffraction phenomenon. We use small apperture in the form of single slit, double slit, grating and small circular aperture. From interference-diffraction pattern shown at the screen, we calculated the wavelength of laser used in this experiment, the slit width, the diameter of circular apperture and the distance between slits. Compared to direct measurement of the slit width, the diameter of the circular aperture and the distance between slits, there are discrepancies about 4% to 11 %. These discrepancies are mainly contributed by un-accurate measurements in the interference pattern due to unclear images.